Scientific Opinion on the substantiation of health claims related to lutein and maintenance of normal vision (ID 1603, 1604, further assessment) pursuant to Article 13(1) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to provide a scientific opinion on a list of health claims pursuant to Article 13 of Regulation (EC) No 1924/2006 in the framework of further assessment related to lutein and maintenance of normal vision. The food constituent that is the subject of the claim, lutein, is sufficiently characterised. The claimed effect, maintenance of normal vision, is a beneficial physiological effect. The proposed target population is the general population. In weighing the evidence, the Panel took into account that one human intervention study in healthy subjects did not show an effect of lutein on visual acuity or glare sensitivity, that the results of this study were inconsistent as regards contrast sensitivity, and that the evidence provided for a mechanism by which lutein could exert the claimed effect in vivo in humans is weak. On the basis of the data presented, the Panel concludes that the evidence provided is insufficient to establish a cause and effect relationship between the consumption of lutein and maintenance of normal vision.